PENDAPAT AL-MAZÂHIB AL-ARBA’AH TENTANG BENTUK SYIRKAH DAN APLIKASINYA DALAM PERSEROAN MODERN - Susamto, Burhanuddin (De Jure: Jurnal Hukum dan Syari'ah, 2014)
The practice of sharia principles in our life is a necessity. A corporation as a part of life is not out of the frame of sharia perspective. The desire to view  the corporation  from the sharia perspective is starting  from the fact that in fiqh muamalah there are some  relevant  contract,  especially  syirkah  contract. Al-mazâhib al-arba'ah through their  books of fiqh  have introduced the similarities and differences of opinion concerning shirkah forms which original law is  allowed according to the Qur'an, the Sunnah and ijma '. Therefore, through this article, the author will reveal again the opinion of the each  schools concerning syirkah  forms and how to implement it in the context of a modern corporation.